Early sport specialization linked to throwing arm function and upper extremity injury history in college baseball players (Sports Health: A Multidisciplinary Approach, 2021)
Background: Evidence suggests that shoulder and elbow injuries account for 31% to 37% of all National Collegiate Athletic Association (NCAA) baseball injuries, and up to 69% of NCAA baseball injuries are the result of noncontact and overuse mechanisms. Early sport specialization may contribute to the high rates of upper extremity injuries in college baseball players. Hypothesis: Higher specialization by age 13 years would be associated with worse subjective throwing arm function and a greater history of shoulder and elbow injury. Study Design: Cohort study. Level of Evidence: Level 2. Methods: Survey data were collected from college baseball players (N = 129) during midseason of the spring 2019 baseball season. Participants were stratified in low, moderate, and high specialization groups based on a 3-criteria sports specialization questionnaire. Participants` throwing arm function was measured using the Functional Arm Scale for Throwers and the Kerlan-Jobe Orthopaedic Clinic shoulder and elbow questionnaires. Participants` history of a shoulder or elbow injury that resulted in missing =2 weeks of baseball activity at any point in their baseball career was also collected. Results: The high specialization group reported worse subjective throwing arm function on the Functional Arm Scale for Throwers questionnaire than the low (P = 0.03) and moderate (P = 0.01) specialization groups. The high specialization group was over 5 times more likely to report a history of shoulder injury than the moderate (odds ratio [OR] = 5.42; 95% CI [1.71, 17.2]; P = 0.004) and low (OR = 5.20; 95% CI [1.87, 14.5]; P = 0.002) specialization groups, and over 3 times more likely to report a history of elbow injury than the moderate specialization group (OR = 3.77; 95% CI [1.05, 13.6]; P = 0.04). Conclusion: College baseball players that were highly specialized by age 13 years reported worse subjective throwing arm function and were more likely to have a history of upper extremity injury than players that were moderate or low specialization. Clinical Relevance: Early specialization in baseball may be detrimental to long-term upper extremity health in college baseball players.